Integrated Farming System (IFS): A Review - Khobragade, Shweta; Mohapatra, Sanghamitra; Mahananda, M.; Singh, Aarti; Singh, Anita (International Journal of Economic Plants, 2021)
Adoption of Integrated Farming System (IFS) leads to sustainability and stability in farm income through multiple enterprises that aim at maximum utilization of available natural resources to meet the family needs. It aims at generating a threshold level of farm income required for the farm family to maintain sustained interest in farming thus preventing migration of people from the farming sector. Integrated Farming System which combines activities of food-crop farming with horticulture, animal husbandry, fisheries, forestry and other science related to farming on the same field at the same or almost the same time needs to be developed as a solution to food security problem resulting from decreasing food productivity and climate change. IFS itself is important for sustainable development of farmer by improving yield, economic return, employment generation, nutritional security and livelihood.